2021
DOI: 10.48550/arxiv.2111.15406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing a leptophobic top-colour model with cross section measurements and precise signal and background predictions: a case study

M. M. Altakach,
J. M. Butterworth,
T. Ježo
et al.

Abstract: The sensitivity of particle-level fiducial cross section measurements from ATLAS, CMS and LHCb to a leptophobic top-colour model is studied. The model has previously been the subject of resonance searches. Here we compare it directly to state-of-the-art predictions for Standard Model top quark production and also take into account next-to-leading order predictions for the new physics signal. We make use of the Contur framework to evaluate the sensitivity of the current measurements, first under the default Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…This procedure is then repeated for each set of parameter values resulting in a map of CL exclusions (more information about Contur and its statistical method used to perform the exclusion procedure can be found in [34]). Many studies were performed using the Contur toolkit to check different BSM scenarios [35][36][37][38] and it was shown that limits from precision measurements of SM processes can be more constraining than BSM searches at the LHC in some parts of the parameter space [39]. In this work, we use Contur to set limits on the parameter space of our model.…”
Section: Jhep03(2023)182mentioning
confidence: 99%
“…This procedure is then repeated for each set of parameter values resulting in a map of CL exclusions (more information about Contur and its statistical method used to perform the exclusion procedure can be found in [34]). Many studies were performed using the Contur toolkit to check different BSM scenarios [35][36][37][38] and it was shown that limits from precision measurements of SM processes can be more constraining than BSM searches at the LHC in some parts of the parameter space [39]. In this work, we use Contur to set limits on the parameter space of our model.…”
Section: Jhep03(2023)182mentioning
confidence: 99%
“…This procedure is then repeated for each set of parameter values resulting in a map of CL exclusions (more information about Contur and its statistical method used to perform the exclusion procedure can be found in [186]). Many studies were performed using the Contur toolkit to check different BSM scenarios [187,188,189,190] and it was shown that limits from precision measurements of SM processes can be more constraining than BSM searches at the LHC in some parts of the parameter space [191]. In this chapter, we use Contur to set limits on the parameter space of our model.…”
Section: Fiducial Measurements Of Sm Processes Using Conturmentioning
confidence: 99%